Evolution and the fate of humankind - Corning, Peter A. 1935- (Cambridge University Press, 2025)
In recent years we have come to understand better the forces that have shaped biological evolution over the course of time. Evolved purposiveness (teleonomy) in living systems themselves has been an important influence. Cooperative effects (synergies) of various kinds have also been influential. And the bioeconomics (functional costs and benefits) have been important constraints. Now we are facing a mounting survival crisis that may determine the future of life on Earth. We need to make a major course change, utilizing our insights into these important influences. Here is a review, and a 'prescription.'
Title from publisher's bibliographic system (viewed on 17 Feb 2025)
Keywords: Evolution (Biology) / Philosophy